2010
DOI: 10.1017/s136898000999320x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is endemic in Middle Eastern sportsmen

Abstract: Objective: While vitamin D deficiency is well recognized in Middle Eastern women as a result of cultural norms of remaining covered, Middle Eastern men are an under-reported group. Vitamin D is now known to have multiple effects, including an impact on muscle function, thereby increasing the relevance for sportsmen. The aim of the present study was to evaluate serum 25-hydroxyvitamin D (25(OH)D) levels in young male Middle Eastern athletes. Design: Cross-sectional study. Setting: Qatar Orthopaedic and Sports M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 50 publications
8
79
1
1
Order By: Relevance
“…17 By comparison, in Middle Eastern national level athletes from a variety of sports, 93% of athletes were noted to be deficient and, in Australia, 33% of 18 gymnasts were found to be deficient. 18,19 In our cohort, skin colour and sex were noted to be significant independent predictors of vitamin D status. The remarkable prevalence of deficiency in 54% of dark-skinned female athletes (and insufficient levels in a further 31%) is still comparable with some published literature in older groups of a similar skin colour.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…17 By comparison, in Middle Eastern national level athletes from a variety of sports, 93% of athletes were noted to be deficient and, in Australia, 33% of 18 gymnasts were found to be deficient. 18,19 In our cohort, skin colour and sex were noted to be significant independent predictors of vitamin D status. The remarkable prevalence of deficiency in 54% of dark-skinned female athletes (and insufficient levels in a further 31%) is still comparable with some published literature in older groups of a similar skin colour.…”
Section: Discussionmentioning
confidence: 51%
“…[18][19][20] Serum 25(OH)D is widely accepted as a biomarker for vitamin D status. 21 While some debate persists as to optimal levels of 25(OH)D for health, it is generally accepted that levels of 20 -30 mcg/l represent vitamin D insufficiency while levels below 20 mcg/l and 10 mcg/l are defined as deficient and severely deficient, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one would presume that living at lower latitudes would guarantee protection against vitamin D deficiency, a previous study on the adult population residing in south Florida has shown otherwise (11) . Furthermore, vitamin D deficiency is common in India, Australia, Brazil and the Middle East, because of cultural habits and sun avoidance (12)(13)(14)(15)(16)(17) . Our goal was to establish the prevalence of vitamin D deficiency and to assess seasonal variations in vitamin D levels in adult Saudi female out-patients in Riyadh, Saudi Arabia (24842 0 N), an area of year-round sunny weather.…”
mentioning
confidence: 99%
“…So measuring the atlethe's vitamin D level is desirable. Recent studies suggested a vitamin D deficiency in indoor athletes [3] and middleeastern sportsmen [4], on the contrary outdoor cyclists had an adequate vitamin D level [5].…”
Section: Introductionmentioning
confidence: 99%